2022
DOI: 10.3390/ijms24010105
|View full text |Cite
|
Sign up to set email alerts
|

Timing of ICSI with Respect to Meiotic Spindle Status

Abstract: The aim of this study was to evaluate the efficiency of using meiotic spindle (MS) visibility and relative position to the polar body (PB) as indicators of oocyte maturation in order to optimize intracytoplasmic sperm injection (ICSI) timing. This was a cohort study of patients younger than 40 years with planned ICSI, the timing of which was determined by MS status, compared with those without MS evaluation. The angle between PB and MS and MS visibility were evaluated by optical microscope with polarizing filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Researchers found that MS visibility was revealed to be an important parameter for oocyte maturity and when to do ICSI in patients over the age of 35 [ 8 ]. Our case demonstrated MS visualization as a useful parameter for oocyte maturity and ICSI timing.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that MS visibility was revealed to be an important parameter for oocyte maturity and when to do ICSI in patients over the age of 35 [ 8 ]. Our case demonstrated MS visualization as a useful parameter for oocyte maturity and ICSI timing.…”
Section: Discussionmentioning
confidence: 99%